Differential Regulation of the Multiple Flagellins in Spirochetes - Li, Chunhao (American Society for Microbiology (ASM), 2010)
The expression of flagellin genes in most bacteria is typically regulated by the flagellum-specific sigma(28) factor FliA, and an anti-sigma(28) factor, FlgM. However, the regulatory hierarchy in several bacteria that have multiple flagellins is more complex. In these bacteria, the flagellin genes are often transcribed by at least two different sigma factors. The flagellar filament in spirochetes consists of one to three FlaB core proteins and at least one FlaA sheath protein. Here, the genetically amenable bacterium Brachyspira hyodysenteriae was used as a model spirochete to investigate the regulation of its four flagellin genes, flaA, flaB1, flaB2, and flaB3. We found that the flaB1 and flaB2 genes are regulated by sigma(28), whereas the flaA and flaB3 genes are controlled by sigma(70). The analysis of a flagellar motor switch fliG mutant further supported this proposition; in the mutant, the transcription of flaB1 and flaB2 was inhibited, but that of flaA and flaB3 was not. In addition, the continued expression of flaA and flaB3 in the mutant resulted in the formation of incomplete flagellar filaments that were hollow tubes and consisted primarily of FlaA. Finally, our recent studies have shown that each flagellin unit contributes to the stiffness of the periplasmic flagella, and this stiffness directly correlates with motility. The regulatory mechanism identified here should allow spirochetes to change the relative ratio of these flagellin proteins and, concomitantly, vary the stiffness of their flagellar filament.